Factors Associated with Deworming Medication Utilization among Pregnant Women in Benin: Evidence from the Demographic and Health Survey - Daniel Amoak; Satveer Dhillon; Roger Antabe; Yujiro Sano; Isaac Luginaah (Tropical Medicine and Infectious Disease, 2023)
Deworming medication utilization is a useful strategy to reduce the burden of anemia among pregnant women. Yet, we know very little about the prevalence and correlates of deworming medication utilization among pregnant women in sub-Saharan Africa, including Benin. To address this void in the literature, we used the 2017–2018 Benin Demographic and Health Survey and applied logistic regression analysis to explore the demographic, socioeconomic, and healthcare factors associated with deworming medication utilization in Benin. We found that deworming medication coverage was 65% at the national level. We observed that women aged 35–49 years were less likely to use deworming medication compared to those aged 15–24 years (OR = 0.79, p < 0.01). Compared to Christian women, Muslim women (OR = 0.70, p < 0.01) and women of other religions (OR = 0.51, p < 0.01) were also less likely to use deworming medication. Moreover, women with lower levels of education and household wealth, as well as unemployed women, were less likely to use deworming medication in comparison to their educated, richer, and employed counterparts. Women who visited ANC fewer than eight times were also less likely to use deworming medication compared to their counterparts who did so eight times or more (OR = 0.65, p < 0.001). Based on these findings, we discussed several implications for policymakers.